KEWENANGAN KOMISI PEMBERANTAS KORUPSI DALAM MELAKUKAN PENUNTUTAN MONEY LAUNDERING - Roni Efendi (Institut Agama Islam Negeri Batusangkar, 2018)
The tackling of money laundering through the criminal Justice System has not been debatable as long as it is handled by sub-systems in the criminal justice system such as the police and prosecutors since they have been bestowed a clear mandate in law. That raised a question, what about Corruption Eradication Commission or KPK? In Article 6 letter C Act no.30 of 2002 on the Corruption Eradication Commission (Law of KPK) explicitly and clearly revealed that the KPK has a duty to conduct the initial investigation, investigation and prosecution of corruption. That article also did not provide the further explanation. For that reason, the authority of KPK in conducting initial investigation, investigation and prosecution is only regarding the criminal act of corruption.In several corruption cases settling, KPK also often tried to apprehend the perpetrators through the law of prevention and Eradication of Money Laundering Crime. Many People criticized KPK but some gave the appreciation on KPK’s efforts in asset recovery. That was also addressed to KPK on its’ authority in investigating and prosecuting TPPU. In the case of No. 39/Pid.Sus/ TPK/2013/PN.Jkt.Pst with the accused Ahmad Fathanah, Joko Subagion and I made Hendra as 2 (two) members of the judges’ panel stated dissenting opinion. It declared that KPK has the authority to investigate TPU but it is only concerning with the wealth which is suspected from a criminal act of corruption. Actually, the authority to persecute TPPU is on the general attorney. Meanwhile, persecutors of KPK does not have the right to file the indicment and demand of the TPPU. Therefore, the indictment related to money laundering should be declared unacceptable. It brings the writer’s unrest on the criminal law enforcement’s practice. It is especially in the eradication of money laundering since it is supposed that law enforcement does no provide justice for justicia belene, certainty and expediency in asset recovery.